Blood Compatibility of Sulfonated Cladophora Nanocellulose Beads - Igor Rocha (Molecules, 2018)
Sulfonated cellulose beads were prepared by oxidation of Cladophora nanocellulose to 2,3-dialdehyde cellulose followed by sulfonation using bisulfite. The physicochemical properties of the sulfonated beads, i.e., high surface area, high degree of oxidation, spherical shape, and the possibility of tailoring the porosity, make them interesting candidates for the development of immunosorbent platforms, including their application in extracorporeal blood treatments. A desired property for materials used in such applications is blood compatibility; therefore in the present work, we investigate the hemocompatibility of the sulfonated cellulose beads using an in vitro whole blood model. Complement system activation (C3a and sC5b-9 levels), coagulation activation (thrombin-antithrombin (TAT) levels) and hemolysis were evaluated after whole blood contact with the sulfonated beads and the results were compared with the values obtained with the unmodified Cladophora nanocellulose. Results showed that neither of the cellulosic materials presented hemolytic activity. A marked decrease in TAT levels was observed after blood contact with the sulfonated beads, compared with Cladophora nanocellulose. However, the chemical modification did not promote an improvement in Cladophora nanocellulose hemocompatibility in terms of complement system activation. Even though the sulfonated beads presented a significant reduction in pro-coagulant activity compared with the unmodified material, further modification strategies need to be investigated to control the complement activation by the cellulosic materials.